Character Development among Teenagers in Public and Private Educational Institutions in Pakistan: An Empirical Study - Asmara Batool; Farman Ali; Kamran Ahmed (Journal of Islamic Studies and Education, 2026)
Character development is a fundamental objective of education, yet growing emphasis on academic achievement and career preparation has raised concerns about the declining moral and ethical development of adolescents. This study examined whether institutional type commercial (private) or non-commercial (public) influences adolescent character development and Islamic personality in Pakistan. A quantitative comparative cross-sectional design was employed involving 200 secondary school students from commercial and non-commercial educational institutions in Abbottabad, Pakistan. Data were collected using an adapted Character-Building Scale and the Integrative Islamic Personality Inventory (IIPI). Descriptive statistics, independent-samples t-tests, Pearson correlation, and Cohen's d were performed using IBM SPSS Statistics. The results revealed no statistically significant difference in character-building scores between students from commercial and non-commercial schools (t = −0.95, p = .343), with a negligible effect size (Cohen's d = −0.13) and a very weak correlation between institutional type and character outcomes (r = −0.073). Descriptive findings indicated relatively high levels of moral conscience, conflict resolution, prayer, faith-driven morality, and modesty, whereas academic integrity, decision making, empathy, and conceptions of success received comparatively lower ratings. These findings suggest that adolescents' character development is influenced more by ecological factors including family, school culture, peer relationships, and digital environments than by institutional classification alone. From an Islamic educational perspective, the study reinforces the importance of integrating akhlaq-based education with supportive family and school environments to cultivate ethical behavior. The findings contribute empirical evidence from Pakistan and provide practical implications for educators and policymakers seeking to strengthen holistic character education in both Islamic and secular educational contexts.